UNITY: Building Bridges in a Hyperconnected World - Mokkhuntod, Jaruwan; Phuengpha , Noppawan (Universitas Muhammadiyah Sidoarjo, 2024)
In today's interconnected global landscape, trust is the fundamental element that bridges communication gaps, ensures collaboration, and supports the successful operation of societies and economies. The rapid advancement of digital technology and the rise of hyperconnectivity allow individuals and organizations to interact without borders, yet these advancements also create new challenges for building and maintaining trust. This journal explores how trust can be fostered in a hyperconnected world, focusing on the